Evaluation of step’s slope on energy dissipation in stepped spillway - Heidari, Ali; Ghasemi, Poria (International Journal of Engineering and Technology, 2014)
Stepped spillways are kind of dissipative structures used in rivers with steep slopes to reduce the flow energy and also the scouring potential of water. This dissipation is caused through diffusion along the spillway. The reduction of energy also leads to optimize the still basin geometry and performance downstream, and thus make the project more economic. In this paper, the hydraulic behaviour of stepped spillway is investigated based on kinetic energy. The results show that the average mean kinetic energy decreases upon an appraise in steps‘s slope. Finally, horizontal steps are proposed. Keywords: Stepped Spillway, Mean Kinetic Energy, Dissipation, and Steps’s Slope.